ANALISIS KUALITAS PELAYANAN PEMERIKSAAN RT-PCR TERHADAP KEPUASAN PASIEN DI UPDT LABORATORIUM KESEHATAN DAERAH KABUPATEN MOJOKERTO - M. Aris Munandar; Eka Diah Kartiningrum; Rifaatul Laila Mahmudah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Improving the quality of service is an important point as the end point of the overall government administration reform. During the Covid 19 pandemic, visits to laboratories were expected that each clinical laboratory must meet the criteria for organization, space and facilities, equipment, specimens, examination methods, quality, security, recording and reporting properly. This study aimed to determine the effect of the quality of RT-PCR examination services at the UPTD Health Laboratory in Mojokerto Regency in 2022. The study design was a cross-sectional study. The population in this study were all patients carrying out RT-PCR examinations at the UPTD Regional Health Laboratory of Mojokerto Regency in 2022 with an average population in 2 months of 60 patients with a sample of 38 respondents. Data was collected using a questionnaire and then analyzed using linear regression. The results of the study explained that the quality of RT-PCR examination services on patient satisfaction at the Mojokerto District Health Laboratory UPTD in 2022 had a positive effect on patient satisfaction, which means that the better the quality of service performed by the UPTD Mojokerto District Health Laboratory, the higher patient satisfaction. Judging from the simple linear regression test of service quality on consumer (patient) satisfaction meets the requirements because the significance value is 0.003 <0.05, it can be concluded that variable X (service quality) affects variable Y (patient satisfaction). support from the local government through the Mojokerto District Health Office in terms of physical improvement of the UPTD Mojokerto District Health Laboratory and improving the quality of health services.